2020
DOI: 10.3390/su12187377
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Factors Affecting the Performance of Rural Road Projects in Colombia

Abstract: Rural roads play an indispensable role in economic and social well-being, especially in developing countries, contributing to achieving the Sustainable Development Goals. For this reason, it is necessary to plan these projects properly to guarantee their success. In this line, the objective of this research is to identify significant variables generating overruns in time and cost using empirical data of 535 rural road projects in Colombia from 2015 to 2018. Bivariate analysis, with statistical tools like Spear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The authors found a weighted average time deviation of 42.6% and identified that the following exogenous determinants have a substantial impact on time deviations: political, institutional, and governance environment, the legal and institutional environment, and also the economic context. Catalão et al (2021a) found that local government projects have more time deviations than those developed by central government, and they uncovered no evidence that project size influences deviations, in contrast to the previous findings of Gómez-Cabrera et al (2020).…”
Section: Political Control Variablesmentioning
confidence: 77%
See 2 more Smart Citations
“…The authors found a weighted average time deviation of 42.6% and identified that the following exogenous determinants have a substantial impact on time deviations: political, institutional, and governance environment, the legal and institutional environment, and also the economic context. Catalão et al (2021a) found that local government projects have more time deviations than those developed by central government, and they uncovered no evidence that project size influences deviations, in contrast to the previous findings of Gómez-Cabrera et al (2020).…”
Section: Political Control Variablesmentioning
confidence: 77%
“…(2021a) found that local government projects have more time deviations than those developed by central government, and they uncovered no evidence that project size influences deviations, in contrast to the previous findings of Gómez‐Cabrera et al. (2020).…”
Section: Literature Reviewmentioning
confidence: 80%
See 1 more Smart Citation
“…Cost deviations in construction projects, including natural disaster prevention projects (NDPPs), significantly impact project success [7,8]. These deviations pose financial risks and challenges, especially for clients and contractors [9].…”
Section: Construction Project Cost Deviation and Risk Management Theorymentioning
confidence: 99%
“…In the context of India, Raut et al [13] investigate the influence of time, cost, and quality on cost deviation, particularly in road and highway projects. Gómez Cabrera [8] from Colombia highlights the impact of the competitive bidding process, while Przywara and Rak [12] in Poland examine time variances related to schedule and cost.…”
Section: Deriving Cost Variation Influencing Factorsmentioning
confidence: 99%